Itinerant challenges and newspaper support: The Johannesénske Balletselskab's Norwegian tour 1878-79 - Anne Margrete Fiskvik (Dance Articulated, 2020)
From March 1878 to October 1879, the Johannesénske Balletselskab toured in Norway and thereby gave people in 16 smaller and peripheral towns the opportunity to see ballet for the first time. The main aim of this article is to explore the challenges related to performance venues and lack of audiences that the Johannesénske faced on their 1878-79 tour. The article is mainly based on an investigation of newspaper material from those years documented on microfilm and storied in libraries. The Johannesénske Balletselskab was used to travelling: in various shapes and forms, this ensemble had been on the road for almost thirty years. During their travelling, Norwegian newspapers were highly supportive of their performances and the article discusses how life on the road was made easier through the support of the press. Life on the road could be challenging in several ways and itinerant life has for centuries required adaptability and the ability to deal with changes and obstacles. Some were dramatic, whereas others more mundane in nature. The challenges of itinerant dance ensembles have been little explored in Nordic and European dance scholarship. In fact, itinerant dancers- and dance ensembles have been a marginalized issue and the aim of this article is make amends for this through investigating a few of the hardships that the Johannesénske encountered.